Design, Synthesis and Pharmacological Evaluation of Novel Benzimidazole Derivatives as Anticancer Agents - R.S., Remya (Current Bioactive Compounds, 2022)
Background: Cancer is undoubtedly a major challenge of modern era and is the second leading cause of death in the world. Lung cancer is the second most common cancer and the leading cause of cancer death among men and women. Non-Small Cell Lung Cancer (NSCLC) accounts for 84% of all lung cancer diagnosed. Benzimidazoles are important heterocyclic compounds possessing a variety of biological activities such as anticancer, antioxidant, anti-inflammatory, and analgesic, anti-viral, anti-bacterial, anti-fungal and hypoglycemic activities. Pyrazolines reported antitumor, immunosuppressive, antibacterial and anti tubercular agents. Biological activities of the benzimidazole derivatives depend on the functional group attached to the benzimidazole moiety. Objective: The present research focused on incorporating pyrazoline nucleus into benzimidazole nucleus to form a potent anticancer agent targeting lung cancer therapy. Methods: The in silico novel pyrazoline substituted benzimidazole derivatives were designed. Docking was performed to know the binding interactions of the newer agents with the enzymes. The compounds were found to be active in docking studies synthesized and tested for anticancer activity. In vitro screening of the selected derivatives for anticancer activity by MTT assay method showed very good results. Cytotoxicity of compounds BZ1, BZ2, BZ10 and BZ16 studied against fibrosarcoma and lung cancer cell line. Results: The compound BZ1 showed highest activity against fibrosarcoma and lung cancer cell line. Conclusion: Further studies on these compounds to prove it as a lead compound in cancer therapy should be conducted.
Keywords: docking